"Intermedial Indian Ocean" - a day of music, dance, poetry and more at Reichshof Bayreuth (Readings, Concerts and other events, 2021)
On 13 November 2021, Prof. Dr. Ute Fendler and Prof. Dr. Clarissa Vierke invited the interested public to an exciting and eventful day dedicated to the Indian Ocean. Music, films, dances, photographs and poetry transported the audience to the East African region, whose artistic and medial forms of expression are often shaped by the beautiful landscape and maritime lifestyle in which they were created. In the evening the event even saw the world premiere of filmmaker Harrikrisna Anenden's "Draupadi's veil". ​This recording shows part of the event. The performances of musician Tao Ravao, dancer Luis Sala and a poetry performance of Abdilatif Abdalla and Clarissa Vierke.